The Similarity of Individual Directed and Group Directed Leader Behavior Descriptions - Schriesheim, Chester A. (Academy of Management Journal, 1979)
The similarity between individual directed and group directed leadership descriptions of subordinates was examined among 308 public utility employees. The correlations among the variables revealed extensive similarity in the two sets of leadership descriptions and almost identical correlations with 10 different dependent variables.